Unilateral Blind Ending Ureter with Vesicoureteral Reflux and Associated Renal Agenesis -Multidetector Computed Tomography Imaging Findings - Vasic, Nada G.; Nikolic, Olivera; Boskovic, Tatjana (Urology Journal, 2016)